A Maranao dictionary - Macaraya, Batua A.; McKaughan, Howard P. 1922-. (Manila De La Salle University Press, [and] Summer Institute of Linguistics, 1996)
It includes 8,500 Maranao entries to be able to give the prototypical meaning of Maranao which are either base words or derivations. It also contains an introduction on the grammar of Maranao, to aid the user in identifying base forms. It is more a glossary than a dictionary.
"It is divided into two parts, the Maranao dictionary and English-Maranao Index. This revision of A Maranao Dictionary has been undertaken to take advantage of current computer technology. The revision includes basically a reformatting in a more acceptable dictionary style. The University of Hawaii Press has given permission to publish the revision in the Philippines, a task undertaken by the De La Salle University Press and Summer Institute of Linguistics. The editor believed that giving the prototypical meanings of Maranao, but also the Maranao desiring to increase their knowledge of English."
Part I is a list of 18,000 Maranao entries. Some entries are equivalent to two to four English words or phrases. The Maranao entries are either base words or derivatives. Over 700 Maranao plant names are also included. Part II is a cross reference of Part I for other glosses. The introduction gives a grammar sketch and indicates other devices to make the material as useful as possible.
Earlier ed. entered under: McKaughan, Howard.
Keywords: Maranao language -- English. -- Dictionaries; English language -- Maranao. -- Dictionaries